Long-Term Estrogen Receptor Beta Agonist Treatment Modifies the Hippocampal Transcriptome in Middle-Aged Ovariectomized Rats - Sárvári, Miklós; Kalló, Imre; Hrabovszky, Erik; Solymosi, Norbert; Rodolosse, Annie; Liposits, Zsolt (Frontiers in Cellular Neuroscience, 2016)
Estradiol (E2) robustly activates transcription of a broad array of genes in the hippocampal formation of middle-aged ovariectomized rats via estrogen receptors (ERα, ERβ and G protein-coupled ER). Selective ERβ agonists also influence hippocampal functions, although their downstream molecular targets and mechanisms are not known. In this study, we explored the effects of long-term treatment with ERβ agonist diarylpropionitrile (DPN, 0.05 mg/kg/day, sc.) on the hippocampal transcriptome in ovariectomized, middle-aged (13 month) rats. Isolated hippocampal formations were analyzed by Affymetrix oligonucleotide microarray and quantitative real-time PCR. Four hundred ninety-seven genes fulfilled the absolute fold change higher than 2 (FC>2) selection criterion. Among them 370 genes were activated. Pathway analysis identified terms including glutamatergic and cholinergic synapse, RNA transport, endocytosis, thyroid hormone signaling, RNA degradation, retrograde endocannabinoid signaling and mRNA surveillance. PCR studies showed transcriptional regulation of 58 genes encoding growth factors (Igf2, Igfb2, Igf1r, Fgf1, Mdk, Ntf3, Bdnf), transcription factors (Otx2, Msx1), potassium channels (Kcne2), neuropeptides (Cck, Pdyn), peptide receptors (Crhr2, Oprm1, Gnrhr, Galr2, Sstr1, Sstr3), neurotransmitter receptors (Htr1a, Htr2c, Htr2a, Gria2, Gria3, Grm5, Gabra1, Chrm5, Adrb1) and vesicular neurotransmitter transporters (Slc32a1, Slc17a7). Protein-protein interaction analysis revealed networking of clusters associated with the regulation of growth/troph factor signaling, transcription, translation, neurotransmitter and neurohormone signaling mechanisms and potassium channels. Collectively, the results reveal the contribution of ERβ-mediated processes to the regulation of transcription, translation, neurogenesis, neuromodulation and neuroprotection in the hippocampal formation of ovariectomized, middle-aged rats and elucidate regulatory channels responsible for DPN-altered functional patterns. These findings support the notion that selective activation of ERβ may be a viable approach for treating the neural symptoms of E2 deficiency in menopause.